Selectivity and Efficacy of Herbicides Applied in Pre-Emergence in Cassava Crop - Antonio Gideilson Correia da Silva; Alex Lima Monteiro; Matheus de Freitas Souza; Jesley Nogueira Bandeira; Ester Dos Santos Coelho; Bianca Pietra Santos Diniz; Aurelio Paes Barros; Daniel Valadao Silva (IEEE Access)
The presence of weeds at the beginning of cultivation can negatively affect cassava productivity because of the slow initial development of the crop. To minimize weed interference, pre-emergence herbicides can be used, provided they are selective to crops. In this study, we evaluated the selectivity and efficacy of herbicides applied in pre-emergence of cassava crop in weed control. Two experiments were conducted in the field during the years 2017, 2018 and 2019. Each year, ten different herbicides were evaluated, along and untreated controls. In the 2017 efficacy experiment, the mixture of atrazine + s-metolachlor provided the highest rate of weed control at 42 days after application (DAA) (76%). The herbicides sulfentrazone, flumioxazin, clomazone, s-metolachlor and metribuzin caused the lowest poisonings in 2017, with rates below 20% in all evaluation periods. Diuron and metribuzin reduced cassava yield. In the second experiment, only the combinations of ametryn + clomazone and ametryn + flumioxazin maintained control levels greater than 85% in all evaluations. Cassava plants experienced less than 25% poisoning for all herbicides tested. However, the use of linuron and the application of paraquat alone did not result in yield reductions. Regarding the relative productivity of the roots, in 2017, only ametryn + clomazone did not result in reductions, while in 2018, the combination s-metolachlor + clomazone was the only one that did not reduce productivity. The results indicate selective and effective herbicides can help reduce production costs and increase yield in cassava crops.